2014
DOI: 10.1186/1471-2407-14-331
|View full text |Cite
|
Sign up to set email alerts
|

Epistemology of the origin of cancer: a new paradigm

Abstract: BackgroundCarcinogenesis is widely thought to originate from somatic mutations and an inhibition of growth suppressors, followed by cell proliferation, tissue invasion, and risk of metastasis. Fewer than 10% of all cancers are hereditary; the ratio in gastric (1%), colorectal (3-5%) and breast (8%) cancers is even less. Cancers caused by infection are thought to constitute some 15% of the non-hereditary cancers. Those remaining, 70 to 80%, are called “sporadic,” because they are essentially of unknown etiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 186 publications
(199 reference statements)
2
139
0
Order By: Relevance
“…“Cancer is a complex and heterogeneous set of diseases with no simple definition” [2,106]. The orchestration of cell-cell communication during carcinogenesis is not well understood as it encompasses different feedback loops and both activating and inhibiting paths of different forms of communication, as well as a fine-tuning mechanism and disarrangement.…”
Section: (2) Cell-cell Communication In Microenvironment and Carcinogmentioning
confidence: 99%
See 2 more Smart Citations
“…“Cancer is a complex and heterogeneous set of diseases with no simple definition” [2,106]. The orchestration of cell-cell communication during carcinogenesis is not well understood as it encompasses different feedback loops and both activating and inhibiting paths of different forms of communication, as well as a fine-tuning mechanism and disarrangement.…”
Section: (2) Cell-cell Communication In Microenvironment and Carcinogmentioning
confidence: 99%
“…“Biological processes as well as cell-cell communication and signaling are themselves a multidimensional musical opera in different acts, which are played differently by different symphony orchestras rather than by a soloist. Even the composition of the music, which is needed before it can be played, is still not well understood.” [2]. Achievements in anticancer therapy and as yet unmet opportunities, including the proposal for new anticancer strategies, have recently been reviewed [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enduring curiosity is needed to find answers and to question the existing paradigms (especially the selfgenerated ones). A Danish patient-cohort study on 445,456 patients revealed, for example, that patients with diverticulitis, when compared to healthy controls, have double the risk of cancer [22], an elevation that could be attributed to chronic inflammation [23]. Resection of the sigmoid, after the second event of sigmoid diverticulitis, eliminates this risk.…”
Section: Healthcare Driven By Science As An Engine Of the Broader Ecomentioning
confidence: 99%
“…The alteration of the ECM changes promote the formation of a tumorigenic microenvironment, stimulating angiogenesis through angiogenic factors like VEGF, which determines the beginning of the vascular branches and facilitates metastasis of tumor cells, with infiltration of immune cells and progression of the cancer (64). A sequence of processes, including transition of normal to cancerous cells and later events such as proliferation, migration, invasion, mutations, and angiogenesis have been reported (65). All these steps accompanied by pathogenic stimuli, chronic inflammation, fibrosis, formation of precancerous niches, help the cells escape chronic stress.…”
Section: Proposed Hypothesesmentioning
confidence: 99%